Opportunities and challenges in recurrent diffuse podocytopathy post-transplantation: the critical value of the definition - Nuccitelli, Rachel; Toutoungis, Amadea; Martinelli, Elena; Sanna-Cherchi, Simone; Weins, Astrid; Morris, Heather K.; Bomback, Andrew S.; Batal, Ibrahim (Frontiers in Immunology, 2026)
Diffuse podocytopathy (DP) is a clinical and pathological entity, which comprises minimal change disease and primary focal segmental glomerulosclerosis (FSGS). It is characterized by diffuse podocyte foot process effacement resulting in nephrotic syndrome. Cumulative evidence supports that DP is a complex disease caused by circulating permeability factors. Following kidney transplantation, DP may recur and severely compromise graft survival. However, prior studies aiming to define immune and genetic factors implicated in disease recurrence have been limited by small cohorts and lack of utilizing stringent criteria to define DP. In this report, we briefly review the important advances made in understanding genomic and permeability factors involved in DP in the native kidney and in the transplant setting, focusing on anti-nephrin antibodies. We stress the importance of applying stringent criteria to define patients at risk of post-transplant recurrence and share our experience in a cohort of 281 consecutive kidney transplant recipients with native kidney failure attributed to FSGS or other forms of DP. Applying strict clinicopathologic criteria combining nephrotic syndrome and diffuse foot process effacement at the time of native kidney biopsy to define DP markedly increased recurrence rate from 9% to 36%. Excluding selected patients with monogenic forms of FSGS and those with high-risk APOL1 genotypes further increased recurrence rate to 54%. In conclusion, an accurate diagnosis of DP in the native kidney is crucial to further our understanding of genomic and immunologic predictors of DP recurrence and to ultimately support the development of prophylactic or therapeutic regimens to improve allograft outcomes.